Diversification of Funding Based on Productive Assets as a Strategy for the Economic Self-Reliance of Islamic Boarding Schools - Liqo Mursidah; Mirhabun Nadhir (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The transformation of financing patterns in Islamic boarding schools (pesantren) from external dependence toward internal self-reliance is a crucial issue for institutional sustainability. This study aims to analyze how productive asset management contributes to the economic independence of pesantren and to identify the success factors and challenges encountered in its implementation. A qualitative descriptive approach was employed at Darul Qur’an Islamic Boarding School in Kundur Utara, Riau Islands. Data were collected through in-depth interviews, observations, and documentation involving institutional leaders, business managers, educators, and community members, followed by an interactive analysis model consisting of data reduction, display, and conclusion drawing. The findings reveal that the utilization of productive assets significantly increases independent income and reduces reliance on unstable external funding. Unexpectedly, this process triggers an organic shift toward more professional management practices while fostering student and community empowerment through collective economic participation. However, implementation faces structural constraints, such as limited capital and managerial capacity, alongside cultural resistance toward economic modernization. The implication of this research is that asset-based funding diversification serves as a strategic and sustainable model for enhancing financial autonomy without eroding the traditional religious identity of the pesantren. This study provides a vital reference for policymakers and practitioners to develop